Vapor-phase hydrodeoxygenation of lignin-derived bio-oil over Al-MCM-41 supported Pd-Co and Pd-Fe catalysts - Tran, N.T.T. (Elsevier B.V., 2022)
Fast pyrolysis of lignocellulosic biomass is an attractive process to produce bio-oil as an alternative liquid fuel source. Upgrading of bio-oil via hydrodeoxygenation (HDO) is an important route to accomplish this renewable energy production process. Al-MCM-41 supported Pd, Co and Fe catalysts were evaluated for HDO of guaiacol and lignin-derived bio-oil at atmospheric pressure in a fixed-bed reactor. Bimetallic Pd-Co and Pd-Fe catalysts showed higher HDO yield and stability than the monometallic Co and Fe catalysts. The addition of Pd significantly enhanced the stability of Co and Fe catalysts since it helped reduce the coke formation. The lignin-derived bio-oil mainly contained phenolic compounds which had one to three oxygen atoms. The catalytic upgrading could not only eliminate significantly the oxygen of these phenolic compounds but also reduce the amount of tar and heavy components. Pd-Fe catalyst was recognized as a suitable catalyst for upgrading of lignin-derived bio-oil since it produced more deoxygenated products and less gas-phase yield than Pd-Co catalyst. Â© 2021 Elsevier B.V.